A Case of Prenatal Neurocytoma Associated With ATR-16 Syndrome. - Quadrifoglio, Mariachiara; Faletra, Flavio; Bussani, Rossana; Pecile, Vanna; Zennaro, Floriana; Grasso, Alessandra; Zandonà, Lorenzo; Alberico, Salvatore; Stampalija, Tamara (J Ultrasound Med, 2016)

Intranasal adminsitration of oxytocin in postnatal depression: implications for psychodynamic psychotherapy from a randomized double-blind pilot study. - Clarici, Andrea; Pellizzoni, Sandra; Guaschino, Secondo; Alberico, Salvatore; Bembich, Stefano; Giuliani, Rosella; Short, Antonia; Guarino, Giuseppina; Panksepp, Jaak (Front Psychol, 2015)
Oxytocin is a neuropeptide that is active in the central nervous system and is generally considered to be involved in prosocial behaviors and feelings. In light of its documented positive effect on maternal behavior, we designed a study to ascertain whether oxytocin exerts any therapeutic effects on depressive symptoms in women affected by maternal postnatal depression. A group of 16 mothers were recruited in a randomized double-blind study: the women agreed to take part in a brief course of psychoanalytic psychotherapy (12 sessions, once a week) while also being administered, during the 12-weeks period, a daily dose of intranasal oxytocin (or a placebo). The pre-treatment evaluation also included a personality assessment of the major primary-process emotional command systems described by Panksepp () and a semi-quantitative assessment by the therapist of the mother's depressive symptoms and of her personality. No significant effect on depressive symptomatology was found following the administration of oxytocin (as compared to a placebo) during the period of psychotherapy. Nevertheless, a personality trait evaluation of the mothers, conducted in our overall sample group, showed a decrease in the narcissistic trait only within the group who took oxytocin. The depressive (dysphoric) trait was in fact significantly affected by psychotherapy (this effect was only present in the placebo group so it may reflect a positive placebo effect enhancing the favorable influence of psychotherapy on depressive symptoms) but not in the presence of oxytocin. Therefore, the neuropeptide would appear to play some role in the modulation of cerebral functions involved in the self-centered (narcissistic) dimension of the suffering that can occur with postnatal depression. Based on these results, there was support for our hypothesis that what is generally defined as postnatal depression may include disturbances of narcissistic affective balance, and oxytocin supplementation can counteract that type of affective disturbance. The resulting improvements in well-being, reflected in better self-centering in post-partuent mothers, may in turn facilitate better interpersonal acceptance of (and interactions with) the child and thereby, improved recognition of the child's needs.

Is "option B+" also being adopted in pregnant women in high-income countries? Temporal trends from a national study in Italy. - Floridia, Marco; Guaraldi, Giovanni; Ravizza, Marina; Tibaldi, Cecilia; Pinnetti, Carmela; Maccabruni, Anna; Molinari, Atim; Liuzzi, Giuseppina; Alberico, Salvatore; Meloni, Alessandra; Rizzi, Laura; Dalzero, Serena; et al. (Clin Infect Dis, 2015)
Keywords: Anti-Retroviral Agents; Antiretroviral Therapy, Highly Active; Developed Countries; Female; HIV Infections; Humans; Infant, Newborn; Italy; Patient Acceptance of Health Care; Pregnancy; Pregnancy Complications, Infectious

Risk-adjusted operative delivery rates and maternal-neonatal outcomes as measures of quality assessment in obstetric care: a multicenter prospective study. - Maso, Gianpaolo; Monasta, Lorenzo; Piccoli, Monica; Ronfani, Luca; Montico, Marcella; De Seta, Francesco; Parolin, Sara; Businelli, Caterina; Travan, Laura; Alberico, Salvatore (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Although the evaluation of caesarean delivery rates has been suggested as one of the most important indicators of quality in obstetrics, it has been criticized because of its controversial ability to capture maternal and neonatal outcomes. In an "ideal" process of labor and delivery auditing, both caesarean (CD) and assisted vaginal delivery (AVD) rates should be considered because both of them may be associated with an increased risk of complications. The aim of our study was to evaluate maternal and neonatal outcomes according to the outlier status for case-mix adjusted CD and AVD rates in the same obstetric population. METHODS: Standardized data on 15,189 deliveries from 11 centers were prospectively collected. Multiple logistic regression was used to estimate the risk-adjusted probability of a woman in each center having an AVD or a CD. Centers were classified as "above", "below", or "within" the expected rates by considering the observed-to-expected rates and the 95% confidence interval around the ratio. Adjusted maternal and neonatal outcomes were compared among the three groupings. RESULTS: Centers classified as "above" or "below" the expected CD rates had, in both cases, higher adjusted incidence of composite maternal (2.97%, 4.69%, 3.90% for "within", "above" and "below", respectively; p = 0.000) and neonatal complications (3.85%, 9.66%, 6.29% for "within", "above" and "below", respectively; p = 0.000) than centers "within" CD expected rates. Centers with AVD rates above and below the expected showed poorer and better composite maternal (3.96%, 4.61%, 2.97% for "within", "above" and "below", respectively; p = 0.000) and neonatal (6.52%, 9.77%, 3.52% for "within", "above" and "below", respectively; p = 0.000) outcomes respectively than centers with "within" AVD rates. CONCLUSIONS: Both risk-adjusted CD and AVD delivery rates should be considered to assess the level of obstetric care. In this context, both higher and lower-than-expected rates of CD and "above" AVD rates are significantly associated with increased risk of complications, whereas the "below" status for AVD showed a "protective" effect on maternal and neonatal outcomes.

Diabetes in pregnancy: timing and mode of delivery. - Maso, Gianpaolo; Piccoli, Monica; Parolin, Sara; Restaino, Stefano; Alberico, Salvatore (Curr Diab Rep, 2014)
Diabetes in pregnancy represents a risk condition for adverse maternal and feto-neonatal outcomes and many of these complications might occur during labor and delivery. In this context, the obstetrician managing women with pre-existing and gestational diabetes should consider (1) how these conditions might affect labor and delivery outcomes; (2) what are the current recommendations on management; and (3) which other factors should be considered to decide about the timing and mode of delivery. The analysis of the studies considered in this review leads to the conclusion that the decision to deliver should be primarily intended to reduce the risk of stillbirth, macrosomia, and shoulder dystocia. In this context, this review provides useful information for managing specific subgroups of diabetic women that may present overlapping risk factors, such as women with insulin-requiring diabetes and/or obesity and/or prenatal suspicion of macrosomic fetus. To date, the lack of definitive evidences and the complexity of the problem suggest that the "appropriate" clinical management should be customized according with the clinical condition, the type and mode of intervention, its consequences on outcomes, and considering the woman's consent and informed decisions.
Keywords: Delivery, Obstetric; Diabetes Mellitus; Diabetes, Gestational; Female; Humans; Pregnancy; Pregnancy Complications

The implications of diagnosis of small for gestational age fetuses using European and South Asian growth charts: an outcome-based comparative study. - Maso, Gianpaolo; Jayawardane, Mathota A M M; Alberico, Salvatore; Piccoli, Monica; Senanayake, Hemantha M (ScientificWorldJournal, 2014)
The antenatal condition of small for gestational age (SGA) is significantly associated with perinatal morbidity and mortality and it is known that there are significant differences in birth weight and fetal size among different populations. The aim of our study was to assess the impact on outcomes of the diagnosis of SGA according to Bangladeshi and European antenatal growth charts in Sri Lankan population. The estimated fetal weight before delivery was retrospectively reviewed according to Bangladeshi and European growth references. Three groups were identified: Group 1-SGA according to Bangladeshi growth chart; Group 2-SGA according to European growth chart but not having SGA according to Bangladeshi growth chart; Group 3-No SGA according to both charts. There was a difference in prevalence of SGA between Bangladeshi and European growth charts: 12.7% and 51.7%, respectively. There were statistically significant higher rates in emergency cesarean section, fetal distress in labour, and intrauterine death (P < 0.001) in Group 1 compared with Group, 2 and 3. No differences of outcomes occurred between Groups 2 and 3. Our study demonstrated that only cases diagnosed as SGA according to population-based growth charts are at risk of adverse outcome. The use of inappropriate prenatal growth charts might lead to misdiagnosis and potential unnecessary interventions.
Keywords: Asian Continental Ancestry Group; Bangladesh; Birth Weight; Europe; European Continental Ancestry Group; Female; Fetal Growth Retardation; Growth Charts; Humans; Infant, Newborn; Infant, Small for Gestational Age; Pregnancy; Prognosis; Sri Lanka

The role of gestational diabetes, pre-pregnancy body mass index and gestational weight gain on the risk of newborn macrosomia: results from a prospective multicentre study. - Alberico, Salvatore; Montico, Marcella; Barresi, Valentina; Monasta, Lorenzo; Businelli, Caterina; Soini, Valentina; Erenbourg, Anna; Ronfani, Luca; Maso, Gianpaolo (BMC Pregnancy Childbirth, 2014)
BACKGROUND: It is crucial to identify in large population samples the most important determinants of excessive fetal growth. The aim of the study was to evaluate the independent role of pre-pregnancy body mass index (BMI), gestational weight gain and gestational diabetes on the risk of macrosomia. METHODS: A prospective study collected data on mode of delivery and maternal/neonatal outcomes in eleven Hospitals in Italy. Multiple pregnancies and preterm deliveries were excluded. The sample included 14109 women with complete records. Associations between exposure variables and newborn macrosomia were analyzed using Pearson's chi squared test. Multiple logistic regression models were built to assess the independent association between potential predictors and macrosomia. RESULTS: Maternal obesity (adjusted OR 1.7, 95% CI 1.4-2.2), excessive gestational weight gain (adjusted OR 1.9, 95% CI 1.6-2.2) and diabetes (adjusted OR 2.1, 95% CI 1.5-3.0 for gestational; adjusted OR 3.0, 95% CI 1.2-7.6 for pre-gestational) resulted to be independent predictors of macrosomia, when adjusted for other recognized risk factors. Since no significant interaction was found between pre-gestational BMI and gestational weight gain, excessive weight gain should be considered an independent risk factor for macrosomia. In the sub-group of women affected by gestational or pre-gestational diabetes, pre-gestational BMI was not significantly associated to macrosomia, while excessive pregnancy weight gain, maternal height and gestational age at delivery were significantly associated. In this sub-population, pregnancy weight gain less than recommended was not significantly associated to a reduction in macrosomia. CONCLUSIONS: Our findings indicate that maternal obesity, gestational weight gain excess and diabetes should be considered as independent risk factors for newborn macrosomia. To adequately evaluate the clinical evolution of pregnancy all three variables need to be carefully assessed and monitored.
Keywords: Adolescent; Adult; Birth Weight; Body Height; Body Mass Index; Diabetes, Gestational; Female; Fetal Macrosomia; Gestational Age; Humans; Infant, Newborn; Italy; Middle Aged; Obesity; Pregnancy; Pregnancy in Diabetics; Prospective Studies; Risk Factors; Weight Gain; Young Adult

The clinical interpretation and significance of electronic fetal heart rate patterns 2 h before delivery: an institutional observational study. - Maso, Gianpaolo; Businelli, Caterina; Piccoli, Monica; Montico, Marcella; De Seta, Francesco; Sartore, Andrea; Alberico, Salvatore (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the clinical significance of intrapartum fetal heart rate (FHR) monitoring in low-risk pregnancies according to guidelines and specific patterns. METHODS: An obstetrician, blinded to neonatal outcome, retrospectively reviewed 198 low-risk cases that underwent continuous electronic fetal monitoring (EFM) during the last 2 h before delivery. The tracings were interpreted as normal, suspicious or pathological, according to specific guidelines of EFM and by grouping the different FHR patterns considering baseline, variability, presence of decelerations and bradycardia. The EFM groups and the different FHR-subgroups were associated with neonatal acid base status at birth, as well as the short-term neonatal composite outcome. Comparisons between groups were performed with Kruskal-Wallis test. Differences among categorical variables were evaluated using Fisher's exact test. Significance was set at p < 0.05 level. RESULTS: Significant differences were found for mean pH values in the three EFM groups, with a significant trend from "normal" [pH 7.25, 95 % confidence interval (CI) 7.28-7.32] to "pathological" tracings (pH 7.20, 95 % CI 7.17-7.13). Also the rates of adverse composite neonatal outcome were statistically different between the two groups (p < 0.005). Among the different FHR patterns, tracings with atypical variable decelerations and severe bradycardia were more frequently associated with adverse neonatal composite outcome (11.1 and 26.7 %, respectively). However, statistically significant differences were only observed between the subgroups with normal tracings and bradycardia. CONCLUSIONS: In low-risk pregnancies, there is a significant association between neonatal outcome and EFM classification. However, within abnormal tracings, neonatal outcome might differ according to specific FHR pattern.
Keywords: Acidosis; Bradycardia; Female; Fetal Blood; Fetal Monitoring; Heart Rate, Fetal; Humans; Hydrogen-Ion Concentration; Infant, Newborn; Labor, Obstetric; Predictive Value of Tests; Pregnancy; Pregnancy Outcome; Retrospective Studies; Single-Blind Method; Statistics, Nonparametric; Time Factors

The effects of uterine fundal pressure (Kristeller maneuver) on pelvic floor function after vaginal delivery. - Sartore, Andrea; De Seta, Francesco; Maso, Gianpaolo; Ricci, Giuseppe; Alberico, Salvatore; Borelli, Massimo; Guaschino, Secondo (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the role of uterine fundal pressure during the second stage of labor (Kristeller maneuver) on pelvic floor dysfunction (urinary and anal incontinence, genital prolapse, pelvic floor strength). METHODS: 522 primiparous women, enrolled 3 months after vaginal delivery, were divided in two groups: group A (297 women) identifies the women who received Kristeller maneuvers with different indications (e.g. fetal distress, failure to progress, mother exhaustion), group B (225 women) the women without maneuver. Participants were questioned about urogynecological symptoms and examined by Q-tip test, digital test, vaginal perineometry and uroflowmetric stop test score. RESULTS: Mediolateral episiotomies, dyspareunia and perineal pain were significantly higher in Kristeller group, whereas urinary and anal incontinence, genital prolapse and pelvic floor strength were not significantly different between the groups. CONCLUSIONS: Kristeller maneuver does not modify puerperal pelvic floor function but increases the rate of episiotomies.
Keywords: Delivery, Obstetric; Dyspareunia; Dystocia; Episiotomy; Fatigue; Fecal Incontinence; Female; Fetal Distress; Humans; Labor Stage, Second; Pain, Postoperative; Pelvic Floor; Pelvic Organ Prolapse; Perineum; Pregnancy; Pressure; Puerperal Disorders; Urinary Incontinence; Uterus

Soluble TRAIL is elevated in recurrent miscarriage and inhibits the in vitro adhesion and migration of HTR8 trophoblastic cells. - Agostinis, Chiara; Bulla, Roberta; Tisato, Veronica; De Seta, Francesco; Alberico, Salvatore; Secchiero, Paola; Zauli, Giorgio (Hum Reprod, 2012)
STUDY QUESTION: What is the potential physiopathological role of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in recurrent miscarriage (RM), characterized by at least three consecutive pregnancy losses. SUMMARY ANSWER: The levels of serum TRAIL immediately after miscarriage in RM patients are significantly elevated with respect to that in first-trimester normal pregnant women, and recombinant TRAIL inhibits the adhesion and migration of HTR8 trophoblastic cells in vitro. WHAT IS KNOWN ALREADY: Both TRAIL and its trans-membrane receptors (TRAIL-R1, TRAIL-R2, TRAIL-R3 and TRAIL-R4) have been documented in the placenta, but their physiopathological role is incompletely understood. STUDY DESIGN, SIZE, DURATION: The study populations consisted of RM patients (n = 80) and first-trimester normal pregnant women (n = 80). Blood samples were obtained within 24 h after abortion (RM) or at gestational 12-week (normal pregnant women). As additional controls, third-trimester normal pregnant women (n = 28) were examined before (within 72 h) and after (within 24 h) partum. PARTICIPANTS/MATERIALS, SETTING, METHODS: The concentrations of TRAIL were analysed in serum samples by ELISA. In parallel, the effect of soluble recombinant TRAIL (0.1-1000 ng/ml) was analysed on the survival of primary extravillus trophoblasts (EVTs) and on the survival, proliferation, adhesion and migration of trophoblastic HTR8 cells. MAIN RESULTS AND THE ROLE OF CHANCE: The circulating levels of TRAIL in RM women (median: 52.5 pg/ml; mean and SD: 55.5 ± 24.4 pg/ml) were significantly higher with respect to first-trimester normal pregnant women (median: 44.9 pg/ml; mean and SD: 47 ± 15.1 pg/ml) and third-trimester normal pregnant women, as assessed before (median: 45.1 pg/ml; mean and SD: 46 ± 12.4 pg/ml) and after partum (median: 35.4 pg/ml; mean and SD: 38 + 17.5 pg/ml). Both primary EVT and HTR8 cells expressed detectable levels of TRAIL death receptors, but exposure to soluble recombinant TRAIL did not induce cell death of trophoblastic cells. On the other hand, TRAIL dose-dependently inhibited the adhesion of HTR8 cells to decidual endothelial cells (DEC) as well as the migration of HTR8 in transwell assays using either fibronectin or DEC. LIMITATIONS, REASONS FOR CAUTION: Although this study suggests that TRAIL might have a pathogenic role in RM by inhibiting both the adhesion and migration capabilities of first trimester trophoblastic cells, there is a possibility that the elevated serum levels of TRAIL in RM are not cause but rather the result of RM. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings together with data of other authors suggest that circulating TRAIL should be further analysed as a potential important biomarker in different physiopathological settings. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by FIRB projects (RBAP11Z4Z9_002 to Giorgio Zauli and RBAP10447J_002 to Paola Secchiero). The authors have no competing interests to declare.
Keywords: Abortion, Habitual; Apoptosis; Cell Adhesion; Cell Line; Cell Movement; Cells, Cultured; Enzyme-Linked Immunosorbent Assay; Female; Humans; Pregnancy; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand; Trophoblasts

Circulating TRAIL shows a significant post-partum decline associated to stressful conditions. - Zauli, Giorgio; Monasta, Lorenzo; Rimondi, Erika; Vecchi Brumatti, Liza; Radillo, Oriano; Ronfani, Luca; Montico, Marcella; D'Ottavio, Giuseppina; Alberico, Salvatore; Secchiero, Paola (PLoS One, 2011)
BACKGROUND: Since circulating levels of TNF-related apoptosis inducing ligand (TRAIL) may be important in the physiopathology of pregnancy, we tested the hypothesis that TRAIL levels change at delivery in response to stressful conditions. METHODS/PRINCIPAL FINDINGS: We conducted a longitudinal study in a cohort of 73 women examined at week 12, week 16, delivery and in the corresponding cord blood (CB). Serum TRAIL was assessed in relationship with maternal characteristics and to biochemical parameters. TRAIL did not vary between 12 (67.6±27.6 pg/ml, means±SD) and 16 (64.0±16.2 pg/ml) weeks' gestation, while displaying a significant decline after partum (49.3±26.4 pg/ml). Using a cut-off decline >20 pg/ml between week 12 and delivery, the subset of women with the higher decline of circulating TRAIL (41.7%) showed the following characteristics: i) nullipara, ii) higher age, iii) operational vaginal delivery or urgent CS, iv) did not receive analgesia during labor, v) induced labor. CB TRAIL was significantly higher (131.6±52 pg/ml) with respect to the corresponding maternal TRAIL, and the variables significantly associated with the first quartile of CB TRAIL (<90 pg/ml) were higher pre-pregnancy BMI, induction of labor and fetal distress. With respect to the biochemical parameters, maternal TRAIL at delivery showed an inverse correlation with C-reactive protein (CRP), total cortisol, glycemia and insulin at bivariate analysis, but only with CRP at multivariate analysis. CONCLUSIONS: Stressful partum conditions and elevated CRP levels are associated with a decrease of circulating TRAIL.
Keywords: Adult; Biological Markers; C-Reactive Protein; Female; Fetal Blood; Fetal Distress; Humans; Labor, Obstetric; Logistic Models; Multivariate Analysis; Postpartum Period; Pregnancy; Pregnancy Outcome; Statistics, Nonparametric; Stress, Physiological; TNF-Related Apoptosis-Inducing Ligand

"GINEXMAL RCT: Induction of labour versus expectant management in gestational diabetes pregnancies". - Maso, Gianpaolo; Alberico, Salvatore; Wiesenfeld, Uri; Ronfani, Luca; Erenbourg, Anna; Hadar, Eran; Yogev, Yariv; Hod, Moshe (BMC Pregnancy Childbirth, 2011)
BACKGROUND: Gestational diabetes (GDM) is one of the most common complications of pregnancies affecting around 7% of women. This clinical condition is associated with an increased risk of developing fetal macrosomia and is related to a higher incidence of caesarean section in comparison to the general population. Strong evidence indicating the best management between induction of labour at term and expectant monitoring are missing. METHODS/DESIGN: Pregnant women with singleton pregnancy in vertex presentation previously diagnosed with gestational diabetes will be asked to participate in a multicenter open-label randomized controlled trial between 38+0 and 39+0 gestational weeks. Women will be recruited in the third trimester in the outpatient clinic or in the Day Assessment Unit according to local protocols. Women who opt to take part will be randomized according to induction of labour or expectant management for spontaneous delivery. Patients allocated to the induction group will be admitted to the obstetric ward and offered induction of labour via use of prostaglandins, Foley catheter or oxytocin (depending on clinical conditions). Women assigned to the expectant arm will be sent to their domicile where they will be followed up until delivery, through maternal and fetal wellbeing monitoring twice weekly. The primary study outcome is the Caesarean section (C-section) rate, whilst secondary measurements are maternal and neonatal outcomes. A total sample of 1760 women (880 each arm) will be recruited to identify a relative difference between the two arms equal to 20% in favour of induction, with concerns to C-section rate. Data will be collected until mothers and newborns discharge from the hospital. Analysis of the outcome measures will be carried out by intention to treat. DISCUSSION: The present trial will provide evidence as to whether or not, in women affected by gestational diabetes, induction of labour between 38+0 and 39+0 weeks is an effective management to ameliorate maternal and neonatal outcomes. The primary objective is to determine whether caesarean section rate could be reduced among women undergoing induction of labour, in comparison to patients allocated to expectant monitoring. The secondary objective consists of the assessment and comparison of maternal and neonatal outcomes in the two study arms. .
Keywords: Adolescent; Adult; Cesarean Section; Diabetes, Gestational; Female; Gestational Age; Humans; Intention to Treat Analysis; Labor, Induced; Patient Selection; Pregnancy; Pregnancy Outcome; Research Design; Watchful Waiting; Young Adult

A multicenter, case-control study on risk factors for antepartum stillbirth. - Facchinetti, Fabio; Alberico, Salvatore; Benedetto, Chiara; Cetin, Irene; Cozzolino, Sabrina; Di Renzo, Gian Carlo; Del Giovane, Cinzia; Ferrari, Francesca; Mecacci, Federico; Menato, Guido; Tranquilli, Andrea L; Baronciani, Dante (J Matern Fetal Neonatal Med, 2011)
OBJECTIVE: As the influence of socio-demographic variables, lifestyle and medical conditions on the epidemiology of stillbirth (SB) is modified by population features, we aimed at investigating the role played by these factors on the incidence of SB in a developed country. STUDY DESIGN: Multivariate logistic regression analysis (OR with 95% CI) was utilized in a prospective multicentre nested case-control study to compare in a 1:2 ratio stillborn of >22 weeks gestation with matched for gestational age live-born (LB) infants. Intrapartum SB were excluded. RESULTS: Two hundred fifty-four consecutive SBs and 497 LBs were enrolled. Socio-demographic variables were equally distributed. Fetal malformations (7.96, 2.69-23.55), severe intrauterine growth restriction (IUGR) (birthweight ≤ 5(th) %ile) (4.32, 2.27?8.24), BMI > 25 (2.87, 1.90-4.33), and preeclampsia (PE, 0.40, 0.21-0.77) were recognized as independent predictors for SB. At term, only BMI > 25 was associated with SB (7.70, 2.9-20.5). CONCLUSION: Fetal malformations, severe IUGR and maternal BMI > 25 were associated with a significant increase in the risk of SB; PE presented instead a protective role. Maternal BMI > 25 was the only risk factor for SB identified in term pregnancies.
Keywords: Adult; Case-Control Studies; Cause of Death; Congenital Abnormalities; Female; Fetal Death; Fetal Growth Retardation; Humans; Infant, Newborn; Male; Obstetric Labor Complications; Pre-Eclampsia; Pregnancy; Risk Factors; Stillbirth; Young Adult

Rubella susceptibility profile in pregnant women with HIV. - Floridia, Marco; Pinnetti, Carmela; Ravizza, Marina; Tibaldi, Cecilia; Sansone, Matilde; Fiscon, Marta; Guaraldi, Giovanni; Guerra, Brunella; Alberico, Salvatore; Spinillo, Arsenio; Castelli, Paula; Dalzero, Serena; et al. (Clin Infect Dis, 2011)
Keywords: Female; HIV Infections; Humans; Pregnancy; Pregnancy Complications, Infectious; Rubella